Implementasi Metode Talqin Dalam Membina Hafalan Al-Quran Santri Tunanetra Di Pesantren Disabilitas Generasi Qurani Cipanas Cianjur - Sriwahyudi, Doni; Kurniawati, Neng; Hidayat, Cep Ramdan (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
One of the processes of learning the Koran is by memorizing it, the talqin method is one solution to enable blind students to memorize the Koran. The formulation of the problem of this research is: 1) How is the implementation of the talqin method for blind students in memorizing the Al-Quran at the Qurani Generation Disability Islamic Boarding School, 2) What are the supporting factors and obstacles to implementing the talqin method for blind students at the Qurani Generation Disability Islamic Boarding School, 3) What are the results or impacts of applying the talqin method in memorizing the Al-Quran for blind students at the Qurani Generation Islamic Boarding School with Disabilities. This type of research is a qualitative type of research, the data collection method uses: 1) Observation, 2) Interview, 3) Documentation. The results of this research show that the implementation of the talqin method in memorizing disabled students at the Qurani Generation Islamic Boarding School with Disabilities, the process begins with a tahfizh teacher modeling reading with certain systematics and repetitions, then the students follow it until they produce reading or memorization as exemplified. Supporting factors for applying the talqin method in developing the memorization of blind students: a) Media and Talqin Method, b) Muhafidz (Teacher), c) Role of Students, d) Role of Accompanying Teachers and Parents, e) Reweads. The constraining factors are facilities and infrastructure. The impact of implementing the talqin method in fostering student memorization at the Qurani Generation Disability Islamic Boarding School is that it makes it easier for blind students to memorize the Qur'an, especially for students who cannot read or use the Braille Al-Quran.